ANALISI KADAR ALP (ALKALINE PHOSPATASE) DAN KHOLINESTERASE AKIBAT LAMA BEKERJA PADA PETUGAS FOGGING DI KOTA DENPASAR - Ni Kadek Mona Fujiastuti Hendriani; Ni Putu Rahayu Artini; I Wayan Tanjung Aryasa (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
Fogging is an effective way to prevent dengue fever in Indonesia. The side effects of fogging can have an impact on its officers by being exposed and inhaled by continuing to treat fumes that contain pesticides. So, that the liver function examination is carried out to determine the increase in ALP  (Alkaline Phospatase ) levels and decrease in cholinesterase levels due to a long time working on fogging officers in Denpasar. This aims to determine whether there is an increase in ALP levels and a decrease in the level of cholinesterase in fogging officers' blood samples. This type of research carried out statistical tests by displaying the lowest, highest value and average test results and deviations standards. From the examination results obtained, it was found that ALP levels in March 2020 with an average of 63.1 ± 0.23 IU / L, while in April 2020 with an average of 98.0 ± 0.23 IU / L, at cholinesterase levels in March 2020 with an average of 5.2 ± 0.01 kU / L, while in April 2020 the average was 6.5 ± 0.01 kU / L. It can be concluded that there was an increase in ALP with an average percentage increase of 0.88% and a decrease in cholinesterase levels in April higher than March, with an average percentage decrease of 0.29%.